KAJIAN ATAS PERBANDINGAN HUKUM PERLINDUNGAN ANAK ANGKAT ATAS PERCERAIAN ORANGTUA ANGKATNYA MENURUT HUKUM ADAT DAN KITAB UNDANG-UNDANG HUKUM PERDATA YANG BERLAKU PADA ETNIS TIONGHOA DI SIBOLGA-TAPANULI TENGAH - YUVINDRI YUVINDRI (PREMISE LAW JURNAL, 2017)
Attention to children has long existed in line with human civilization itself which from day to day progresses. The child is the son of life, the future of the nation and state. Therefore, children need coaching, special guidance in order to grow physically, mentally and spiritually to the fullest. The issues discussed in this thesis are the arrangement of adoption for the ethnic Chinese in Sibolga - Central Tapanuli according to Customary Law and Civil Code, due to any law that can arise to adopted children when their adoptive parents from ethnic Chinese in Sibolga-Tapanuli Tengah are divorced And legal protection of adopted children in connection with the divorce of their adoptive parents from ethnic Chinese in Sibolga - Central Tapanuli. Keywords : Protection, Divorce and Child Lift